Acute Hydrops with Micro-Cornea – an Extremely Rare Condition: A Case Report. Issue 1 (2017) - Chowdhury, Tuhin; Pradhan, Aditya
Purpose: To report the first case of a one-eyed child with micro-cornea, coloboma of iris and acute hydrops without any other disorder of the cornea or systemic disease. Methods: Intracameral injection of perfluoro propane (C3F8) gas was performed under general anaesthesia. Results: Resolution of the hydrops was observed at 1st week of follow-up, which was confirmed by anterior segment optical coherence tomography. Patient was subsequently lost to follow-up. Conclusions: Intracameral injection of perfluoro propane gas is an effective way to quickly resolve acute hydrops. In this specific case, the patient presented with micro-cornea and no other corneal abnormalities.